2015
DOI: 10.1002/cb.1559
|View full text |Cite
|
Sign up to set email alerts
|

The values and motivations behind sustainable fashion consumption

Abstract: The growth in ethical consumption behaviour and greater interest in sustainable fashion from a production side provides grounding for the emergence of a new consumer market for sustainable fashion. To date, however, most studies in this field focus on the production end of the emerging market, with little exploration of the consumers. Of the work, there is on sustainable fashion consumption; the majority discuss perceptions of sustainable fashion by the general population, with little work sampling actual cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
313
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(383 citation statements)
references
References 58 publications
(116 reference statements)
10
313
2
7
Order By: Relevance
“…For example, the environmental goals were stated by terms "organic" [21,22], "biodegradable" [22], and "eco-labelled or recycled material" [23], and social goals were indicated by terms "fair trade" [21,22], "sweatshop-free labor conditions" [22], and "locally" [23]. However, green fashion mainly refers to environmental sustainability [24]. Based on a literature review, we define sustainable fashion as fashion products that benefit, or at least do not harm, our environment and society in their production and consumption processes, and contribute to creating a sustainable future of human beings.…”
Section: Sustainable Fashion and Consumer Purchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the environmental goals were stated by terms "organic" [21,22], "biodegradable" [22], and "eco-labelled or recycled material" [23], and social goals were indicated by terms "fair trade" [21,22], "sweatshop-free labor conditions" [22], and "locally" [23]. However, green fashion mainly refers to environmental sustainability [24]. Based on a literature review, we define sustainable fashion as fashion products that benefit, or at least do not harm, our environment and society in their production and consumption processes, and contribute to creating a sustainable future of human beings.…”
Section: Sustainable Fashion and Consumer Purchase Intentionmentioning
confidence: 99%
“…[24] Sustainable fashion "Sustainable fashion encompasses the myriad of issues of an ethical or environmental nature in the production and consumption of fashion" (p. 150).…”
Section: Sustainable Fashion and Consumer Purchase Intentionmentioning
confidence: 99%
“…Shaw and Shiu [29] explained that consumers pursue ethical consumption both for their own satisfaction and for others, and thus they can experience psychological conflict when those interests collide. In addition, it has been shown that consumers experience conflicts of personal and social values in the context of sustainable food consumption [30], sustainable fashion consumption [31], and ethical consumption considering animal welfare [11,32].…”
Section: Value Conflicts In Socially Responsible Consumptionmentioning
confidence: 99%
“…Colorado State University, 2017). [2] The positioning of specific consumers needs to be more detailed, which means it can be multilevel classified according to consumers' age, gender, health needs, disease characteristics, in particular, the design criteria should be ergonomically correct. Based on the prominent functional characteristics of intelligent technology, the target consumer groups have more clear functional design requirements.…”
Section: The Consumer Positioning and Function Design Of Smart Clothimentioning
confidence: 99%